2010
DOI: 10.1080/00071668.2010.508486
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between polymorphisms inADSLandGARS-AIRS-GARTgenes with inosine 5′-monophosphate (IMP) contents in Beijing-you chickens

Abstract: 1. The association of single nucleotide polymorphisms identified within the ADSL (adenylosuccinate lyase deficiency) gene and GARS-AIRS-GART (glycinamide ribonucleotide synthetase-aminoimidazole ribonucleotide synthetase-glycinamide ribonucleotide transformylase) gene with the content of inosine 5'-monophosphate (IMP) was studied in a population of male Beijing-you (BJY) chickens slaughtered at 90 d of age. 2. A single nucleotide polymorphism in exon 2 of the ADSL gene had an effect on IMP content. Chickens in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…Recent studies have reported that ADSL and GARS-AIRS-GART affect IMP content in chickens (Shu et al, 2009;Ye et al, 2010). In this study, ADSL and GARS-AIRS-GART had high expression levels in LL and low expression levels in heart and liver.…”
Section: Effect Of Different Tissues On Gene Expressionmentioning
confidence: 64%
See 1 more Smart Citation
“…Recent studies have reported that ADSL and GARS-AIRS-GART affect IMP content in chickens (Shu et al, 2009;Ye et al, 2010). In this study, ADSL and GARS-AIRS-GART had high expression levels in LL and low expression levels in heart and liver.…”
Section: Effect Of Different Tissues On Gene Expressionmentioning
confidence: 64%
“…Single nucleotide polymorphisms in ADSL, a gene that codes for adenylosuccinate lyase, and in GARS-AIRS-GART, a gene that codes for glycinamide ribonucleotide-aminoimidazole ribonucleotide synthetaseglycinamide ribonucleotide transformylase, affect muscle inosine monophosphate (IMP) content in chickens (Shu et al, 2007(Shu et al, , 2009Ye et al, 2010). The gene DGAT1, which affects IMP content by increasing triglyceride levels in pig muscle (Nonneman and Rohrer, 2002), is associated with improved meat quality in Landrace swine.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle IMP content had a similar trend to that of mRNA levels of ADSL, AMPD1, and ATIC. Muscle IMP content is affected by the expression of ATIC or AMPD1 in swine [4] [18] [19] and by the expression of ADSL, AMPD1, and ATIC in chicken [5] [20] [34] reported that the expression of ADSL in Danish landrace was lower than that in Wei pig and higher than that in Anqing six-white pig without significant differences. Additionally, the expression of ADSL in Wei pig was higher than that in Anqing six-white pig, which was not consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on IMP metabolism have mainly focused on the polymorphisms and mRNA levels of AMPD1, ADSL, and ATIC and their association with IMP content in chickens [7]- [16]. The study findings revealed that the expression levels of these genes are higher in muscle than in other tissues [7] [17] and that IMP content is associated with these three genes [5] [7] [10] [11] [14] [15]. The polymorphisms of ADSL, AMPD1, and ATIC in different swine species and their associations with IMP metabolism have been reported [4] [16] [18] [19] [20].…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al (2010), for the Beijing You chicken, found 1 polymorphism locus (C3484T); the breast IMP content was significantly different among genotypes. Our results confirmed that C3484T mutations cause differences in IMP and that IMP content is lower in the homologous mutant TT type, which is consistent with the results of Ye.…”
Section: Hrm Technique and Its Application For Detecting Genotypes Afmentioning
confidence: 99%